Desenvolvimento de liderança e competências: a experiência de universitários com a livre iniciativa - Cardoso, Paulo André Costa (2011)
This dissertation aims to analyse the development of leadership promoted through the Sife Experience of Team SIFE CESUPA Center University of Pará 2009/2010. The main objectives are to investigate the role of SIFE on the education of leaders and the motivations of those who participate in the SIFE Experience , having as theoretical references the studies of leadership and the management of human resources by competences. Students in Free Enterprise (SIFE) is a non-profit organization that seeks to change the reality of communities through the development of leadership, based on projects that are built under business values. In other words, such principles aim to develop the mentality of free enterprise among university students. The way to achieve the development of leaders is through an annual competition among university students, who are organized as teams. Teams are assessed by judges (business leaders) in two categories, national and worldwide. The first chapter discusses the management of human resources. The research with members of SIFE explores the development of competences related to leadership. However, the debate is over its models, and this work picks management of competences for developing competences and management subsystems, which includes recruitment and maintenance of people within organizations. Studies on the management of human resources through competences differ among three fields, American, French and Brazilian. Due to the objective of this research, the second theoretical chapter studies the subject of leadership. It shows the development of theories and the perspective of leadership and its role within organizations. This work also approaches schools of leadership such as trait, behavioral, contingency and neo-emergent theories. The second chapter finishes with the analysis of leadership concepts within the case of SIFE. In order to achieve the objective of this research, interviews were carried with leaders of Team SIFE CESUPA, helping to understand the experiences from the point of view of members. The methodology used along this study was the analysis of text and categorization over the transcribing of interviews. These interviews analyses reveal that the SIFE experience is important for students to develop competences as communication and planning, though the students are not able to measure the evolution of such competences. This research interviews also show that the motivation to join a team does not arise because of championships, but due to the benefits that appear while helping poor communities and the advantages related to the professional career